Coal fires, steel houses and the man in the moon: local experiences of energy transition - Darby, S (Elsevier, 2017)
Energy transitions involve long-term structural change and are generally presented and discussed in ‘grand narrative’ terms: low carbon, sustainable growth, smart systems. Yet demand for energy services has always been highly distributed and local considerations are also becoming more prominent on the supply side, with developments in distributed electricity generation and heat networks. This paper is based primarily on interviews and observations with low-income householders and their energy advisers, carried out in a district of central Scotland whose economy had depended on coal and paraffin shale mining for over a century. Many older residents had experienced a transition from belonging to fuel-producing communities and handling solid fuels to becoming ‘consumers’ in uneasy and uncomprehending relationships with distant suppliers of gas and electricity. Their stories add texture to ‘grand narratives’ of energy transition, demonstrating, for a particular place and time, some of the complexity and path dependencies of energy systems and how they play out in social and distributional terms. They show how local resources, institutions, social networks and built environment can affect energy services and responses to them, highlighting the role of ‘middle actors’ in an energy advice service as guides to transition.